A, The Effect of Brand Image On Consumer Purchase Decisions on Products Yamaha (Case Study on PT. Alfa Scorpii Faithful Budi) - Prasetyo, Leonardo (ADPEBI, 2022)
Customers' purchasing decisions on the products offered are experiencing a decline where many old consumers have never made repeat purchases of products where consumers usually always look for the latest products from Yamaha when they want to buy motorcycle products. The Yamaha brand seems to give a bad impression on consumers so that when researchers interview about products from Yamaha, consumers are a little indifferent. In addition, there are also various brand images obtained, namely that motorcycles still seem wasteful in using fuel by consumers, have higher prices than competitors with similar products.The purpose of this study was to determine the effect of brand image on purchasing decisions at PT. Alfa Scorpio Medan.The method used in this research is descriptive method, this type of research is quantitative data, primary data obtained through questionnaires. The research population that will be used in the study are all consumers who make purchases at the company during the 2021 period as many as 544 consumers. Because the population used is 544 consumers, the population will be reduced by using the Slovin sampling technique with a 90% confidence level and an error rate of 10% where 85 samples are obtained. The analytical technique used is multiple linear analysis and statistical tests, namely t-test (partial) and F-test (simultaneous) using SPSS (statistical package for the social sciences) software.The test results show that partially the brand image variable has a positive and significant effect on purchasing decisions where the influence given is 22.4%.The conclusion of this study is that partially, the brand image variable has a positive and significant effect on purchasing decisions at PT. Alfa Scorpio Medan.